Dyskusja i spory wokół wprowadzania podwójnych nazw miejscowości na terenie Śląska Opolskiego - Trosiak, Cezary (Przegląd Politologiczny, 2018)
The emergence of a German minority in the western part of OEl¹sk Górny (Upper Silesia, Opolskie Region) in 1989 stirred a discussion, mainly among sociologists and political scientists, on the criteria that would make it possible to solve the issue of justifying this minority’s presence in Poland. At the same time, the leaders of those minority circles faced the task of demonstrating that they were German in ethnic and cultural terms. For both parties it became important to force the Polish Parliament to pass a “minority law” as it came to be called. The battle for the provisions of this act, with varying intensity, lasted until January 2005, when it was signed by the President of Poland and the law entered into force in May of the same year. The adoption of the law on ethnic and national minorities and regional languages enabled minorities to introduce double naming of places where they reside. Initially, this phenomenon was most intense in the Opole part of Górny OEl¹sk triggering a full range of reactions, ranging from the definitely hostile, threatening an outbreak of an ethnic conflict, to treating this phenomenon as an element enhancing the socio-cultural attractiveness of regions inhabited by minorities.